2008
DOI: 10.1099/mic.0.2007/012930-0
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the pehA gene encoding the major polygalacturonase of Xanthomonas campestris by Clp and RpfF

Abstract: Exopolysaccharide and several extracellular enzymes of Xanthomonas campestris pv. campestris (Xcc), the causative agent of black rot in crucifers, are virulence factors. In this study, sequence and mutational analysis has demonstrated that Xcc pehA encodes the major polygalacturonase, a member of family 28 of the glycosyl hydrolases. Using the 59 RACE (rapid amplification of cDNA ends) method, the pehA transcription initiation site was mapped at 102 nt downstream of a Clp (cAMP receptor protein-like protein)-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 46 publications
(53 reference statements)
4
32
1
Order By: Relevance
“…Glycerol or glucose was supplemented (2%) as required. The stress conditions have been described previously (Loprasert et al 1999;Hsiao et al 2008). BrieXy, for high osmolarity, 0.3 M NaCl was added.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Glycerol or glucose was supplemented (2%) as required. The stress conditions have been described previously (Loprasert et al 1999;Hsiao et al 2008). BrieXy, for high osmolarity, 0.3 M NaCl was added.…”
Section: Methodsmentioning
confidence: 99%
“…The virulence of Xcc in cabbage (Brassica oleracea) was estimated after bacteria were introduced into the leaves by leaf clipping method (Hsiao et al 2008). The lesion length was measured 14 days post-inoculation.…”
Section: Pathogenicity Testmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the Clp protein directly binds to the promoter regions of the endoglucanase (engA) and polygalacturonase (pheA) genes of X. campestris, presumably enhancing transcriptional expression [26,28]. Therefore, it is reasonable to assume that ClpXo can also bind to the promoter region of eglXoA.…”
Section: Clpxo Binds To the Promoter Region Of Eglxoamentioning
confidence: 99%